Diagnostic Dilemma of Clear Cell Odontogenic Carcinoma Mimicking Various Pathological Entities: A Case Report and Literature Review - Zayed Asiri; Abdullah Alshahrani; Mohammad Shahul Hameed; Khalil Assiri; Hassan Ahmed Assiri (Clinical Case Reports)
ABSTRACT Clear cell odontogenic carcinoma (CCOC) is an extremely rare malignancy presenting as a swelling in the mandibles of females. This disease can be diagnosed based on immunohistochemical markers, including Pan cytokeratin (CK), p63, CK5, smooth muscle actin, calponin, and S‐100. Treatment can be multidisciplinary, involving surgical removal, radiotherapy, or chemotherapy.